INVESTIGATION OF STEROID CONTENTS IN POULTRY CHICKEN AND FEEDS IN SELECTED POULTRY FARMS IN PORT HARCOURT, NIGERIA - Nwokediri, D I; Duru, R U (Research Journal of Agriculture (RJA), 2025)
Three different poultry feeds and chicken samples (broilers, old layers, and native) were screened for steroid hormones using Gas Chromatography-Mass Spectrometry. The target compounds were first extracted by ultrasonication (US EPA 1698); 10 g of the sample was homogenized with the same mass of anhydrous Na2SO4, and a 30 mL aliquot of a 1:1 dichloromethane (DCM)/n-hexane mixture was added to the homogenate. The mixture was ultrasonicated at 35 °C for 15 min. The process was repeated twice with fresh portions of the solvent mixture on the residue and finally analysed using gas chromatography-mass spectrometry (GC-MS). The GC-MS analysis detected three (3) steroids in the poultry chicken samples, including cortisone, cortisol, and tetrahydrocorticosterone (THS). Cortisone showed concentration (μg/g) values of 0.74 ±0.2 and 0.89±0.01 in the broilers and layers chicken, whereas cortisol showed a mean concentration value of 0.92±0.2 in the broiler chicken only. THS was detected only in the layer chicken with a mean concentration of 0.23±0.21. Seven (7) steroids were detected in the feed samples. Steroids were not detected in the native chicken. The work proclaims that poultry feed is the source of the steroids detected in the meat and some may have been completely metabolised. The detectable steroid hormone levels in chicken were lower than the normal concentrations in humans and are not a consumer health risk as the steroids do not bioaccumulate in the body due to metabolism by the liver and kidney